2020
DOI: 10.1088/1755-1315/459/6/062060
|View full text |Cite
|
Sign up to set email alerts
|

Features of Machine-Technological Stations Organization in the System of Agro-Industrial Production

Abstract: The creation of modern machine-technological stations (MTS) causes a lot of disputes about the effectiveness of their operation. The majority of MTS are commercial enterprises, independent of services consumers, which, in the conditions of decreasing equipment availability of agricultural producers, turned out to be monopolists comparing with them. Agricultural enterprises could not become founders of MTS and do not have the ability to influence on the activities of service enterprises directly. The efforts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As a result of freezing, dough blanks experience enormous loads both inside and on the surface of the dough product, which leads to the formation and appearance of certain shortcomings (table 1), therefore, the correct combination of specially designed improvers and strict adherence to technological parameters can mitigate the negative effect of shock temperatures [7][8][9]. For conventional dough, especially for deep-frozen dough pieces, three groups of factors are the most important and necessary: gas formation, gas retention and rheological properties of the dough.…”
Section: Research Resultsmentioning
confidence: 99%
“…As a result of freezing, dough blanks experience enormous loads both inside and on the surface of the dough product, which leads to the formation and appearance of certain shortcomings (table 1), therefore, the correct combination of specially designed improvers and strict adherence to technological parameters can mitigate the negative effect of shock temperatures [7][8][9]. For conventional dough, especially for deep-frozen dough pieces, three groups of factors are the most important and necessary: gas formation, gas retention and rheological properties of the dough.…”
Section: Research Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the problem of air pollution in the Republic has been accumulating for years. Society is really concerned about the terrible state of industrial waste storage facilities, which are unsafe for human health, soil and atmosphere [9][10][11][12][13]. Reasonable use of natural resources and operational actions of environmental protection will be able to carry out their activities in the circumstances when our relationship with nature will be formed on a legal basis.…”
Section: Discussionmentioning
confidence: 99%
“…Since we are dealing with time series of the studied indicators, to determine the presence of a trend in them, we will apply the method of comparing average levels, dividing the time series into two parts and test the main hypothesis about their equality by applying the Student's t-test [17][18][19][20][21][22][23][24][25][26]. We will test the null hypothesis H0 about a systemic shift in the time series using the Heaviside function and construct a regression equation [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. The significance of the parameter with a dummy variable will mean that the hypothesis of the presence of a systemic shift is accepted.…”
Section: Methodsmentioning
confidence: 99%